Introduction to criminal justice - Travis, Lawrence F.; Edwards, Bradley D. (Routledge/Taylor & Francis Group, 2015)
This introductory core book describes the criminal justice process in the United States -- outlining the decisions, practices, people and issues involved. It provides a solid introduction to the mechanisms of the criminal justice system, with balanced coverage of the issues presented by each facet of the process.